KELAYAKAN FLIPBOOK MATERI KEANEKARAGAMAN HAYATI TUMBUHAN OBAT DESA SEBURING KABUPATEN SAMBAS KALIMANTAN BARAT - Leo, Leo; Syamswisna, Syamswisna; Ariyati, Eka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the feasibility of flipbook media on biodiversity material based on the results of studies of ethnobotany of medicinal plants in the village of Seburing, Sambas regency, West Kalimantan and find out the types of plants in the village of Seburing that are used as medicine by the people of Seburing Village, Sambas Regency, Kalimantan West. This type of qualitative research, the method used is descriptive with the sampling technique using purposive sampling. Data collection techniques using interviews, observation, and documentation. From the results of the study, there were 50 types of medicinal plants consisting of 30 families. The results of the study were then implemented in the form of flipbook media. The flipbook media was tested for feasibility by two lecturers of the Biology FKIP Untan education study program, two Biology high school class teachers, namely SMA 1 Semparuk and SMAN 1 Selatiga in Sambas Regency and one Biology teacher in grade X Senior High School in Pontianak City. Based on the validator's assessment, flipbook is included in the valid category with a total average value of 0.99 validation and is suitable for use as a learning medium on biodiversity material. This research is expected to be able to make the general public, especially the Seburing village community, to always preserve the environment, especially the preservation of plants.Â Keywords: flipbook, medicinal plants, Seburing VillageÂ